2010
DOI: 10.17221/121/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of mould growth on dry sausages

Abstract: Pipek P., Rohlík B.-A., Lojková A., Staruch L. (2010): Suppression of mould growth on dry sausages. Czech J. Food Sci., 28: 258-263.The effects of two antifungal agents (natamycin, potassium sorbate) were compared on the mould growth on the surface of dry sausages (both heat treated and fermented). The mould growth was studied on fermented sausage Prešporska saláma and heat treated dry sausage Vysočina after the production and during the ripening and storage. Different samples were prepared: two natamycin trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…For this reason, the increasing trend is using natural preservatives (in the specific case, natural antifungals) instead of chemically synthetised compounds (Ribes et al, 2018). Among them, natamycin is a natural antifungal agent produced during the fermentation of the bacterium Streptomyces natalensis (Pipek et al, 2010). Some essential oils (EO) from plants such as oregano (Origanum vulgare) and basil (Ocimum basilicum L.) can be used as natural antifungals for the production of dry sausages without having detrimental effects on sensory properties (Martín-Sánchez et al, 2011;Saggiorato et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the increasing trend is using natural preservatives (in the specific case, natural antifungals) instead of chemically synthetised compounds (Ribes et al, 2018). Among them, natamycin is a natural antifungal agent produced during the fermentation of the bacterium Streptomyces natalensis (Pipek et al, 2010). Some essential oils (EO) from plants such as oregano (Origanum vulgare) and basil (Ocimum basilicum L.) can be used as natural antifungals for the production of dry sausages without having detrimental effects on sensory properties (Martín-Sánchez et al, 2011;Saggiorato et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…2 ). It is significantly more effective than sorbate, another commonly used antifungal preservative (Shibata et al 1991 ; Pipek et al 2010 ). When applied on the surface of foods, it does not affect its organoleptic properties (taste, texture and colour), and has prolonged antimicrobial activity, being safe for consumption because its oral absorption is negligible (Juneja et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although PS is generally recognized as safe (GRAS), it has been shown that it has some low degree of toxicity (Hoang & Vu, 2016). For this reason, investigations of natural antifungals (such as chitosan, nisin, natamycin, propolis, essential oils [EOs], and others) are needed (Estévez & Cava, 2006; Mathenjwa, Hugo, Bothma, & Hugo, 2012; Ozturk, 2015; Pipek, Rohlik, Lojková, & Staruch, 2010).…”
Section: Introductionmentioning
confidence: 99%